The Higher Education System: Basic Concepts and Implications for Institutional Governance - Anggraheni, Fani Yunida; Maspiyoh, Iyoh (Universitas Terbuka, 2025)
Higher education has a strategic role in educating the nation's life and increasing global competitiveness. As a system, higher education consists of collaborating components such as inputs, processes, outputs, and outcomes that must be managed in an integrated and sustainable manner. This study aims to describe the basic concept of higher education as a system and analyze its implications for institutional governance. The method used is systematic literature review (SRL) with a qualitative approach. Data collection techniques were carried out by searching various literatures in various databases such as Google Scholar, DOAJ, and ScienceDirect and analyzed using thematic techniques. The results of the study show that the higher education system encourages the transformation of institutional governance from traditional administrative models to data-based and quality-oriented adaptive governance. The implementation of the system allows institutions to improve the quality of governance through the integration of management information systems, strengthening the culture of quality, and collaboration between stakeholders. This system provides benefits in the form of improving the quality of public services, innovation, and productivity, but there are challenges in this system such as low graduate absorption, limited scientific development and regulatory dynamics. It is concluded that higher education as a system is not only a conceptual framework, but also a practical basis for developing adaptive and quality-oriented institutional governance.